Making Ultra‐Tough Nanoceramics by Columnar Submicrocrystals with Three‐Level Micro‐Nano Structures. Issue 14 (7th March 2022) - Yu, Yongdong; Zheng, Yongting; Liu, Xudong; Yuan, Yuchen; He, Xiaodong
Abstract: The low fracture toughness of equiaxed nanocrystalline ceramics is the main bottleneck of its wide range of commercial applications. Here, the authors report a method to overcome this limitation for preparing ultra‐tough nanoceramics from using amorphous and supersaturated Al2 O3 /ZrO2 solid solution micro‐powders, which is fabricated by Al–O2 ultrahigh‐temperature combustion synthesis assisted rapid water cooling. The Al2 O3 /ZrO2 micro‐powders containing amorphous and metastable dendritic solid solutions can induce the three‐level micro‐nano structure (submicro/nano/supra‐nano) of the high‐content (up to 70–90%) columnar submicro‐crystals accompanied with high‐density nanoprecipitation after sintering or annealing, which makes the fracture toughness of Al2 O3 /ZrO2 ceramics with a unique combination of high‐strength and high‐hardness increased by 50–100%. This method is beneficial to microstructural design of high‐performance ceramics and can be widely applied to various ceramic systems, coupled with simplicity, low‐cost, and high‐efficiency, making it suitable to industrially produce large‐sized nanoceramics with specific grain geometry in large quantities. Abstract : This work discovers that the amorphous and supersaturated solid solution structures obtained by melt rapid cooling can induce the three‐level micro‐nano structure (submicro/nano/supra‐nano) of the equiaxed/columnar submicrocrystals accompanied with high‐density nanoprecipitation. Additionally, it demonstrates an approach to prepare strong, tough, and hard nanoceramics, which is very suitable for industrial production of nanoceramics in large quantities.